2010
DOI: 10.1111/j.1462-2920.2010.02251.x
|View full text |Cite
|
Sign up to set email alerts
|

Acid‐tolerant microaerophilic Fe(II)‐oxidizing bacteria promote Fe(III)‐accumulation in a fen

Abstract: The ecological importance of Fe(II)-oxidizing bacteria (FeOB) at circumneutral pH is often masked in the presence of O(2) where rapid chemical oxidation of Fe(II) predominates. This study addresses the abundance, diversity and activity of microaerophilic FeOB in an acidic fen (pH ∼ 5) located in northern Bavaria, Germany. Mean O(2) penetration depth reached 16 cm where the highest dissolved Fe(II) concentrations (up to 140 µM) were present in soil water. Acid-tolerant FeOB cultivated in gradient tubes were mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 71 publications
(108 reference statements)
0
59
0
3
Order By: Relevance
“…S5 in the supplemental material), providing further evidence of autotrophy by FeOB. Although one member of the Gallionella-related group, "Candidatus Nitrotoga arctica," is a nitrite-oxidizing bacterium (60), to date, most isolates related to Gallionella are chemolithoautotrophic microaerophilic FeOB (6,10,17,59), strongly suggesting that the 16S and cbbM sequences also represent this metabolism. The physiological characteristics of OYT1 are similar to those of other freshwater microaerophilic FeOB isolates growing at circumneutral pH, such as R-1, S. lithotrophicus strains ES-1 and LD-1, G. capsiferriformans strain ES-2, and Sideroxydans paludicola strain BrT (6,10,17).…”
Section: Discussionmentioning
confidence: 99%
“…S5 in the supplemental material), providing further evidence of autotrophy by FeOB. Although one member of the Gallionella-related group, "Candidatus Nitrotoga arctica," is a nitrite-oxidizing bacterium (60), to date, most isolates related to Gallionella are chemolithoautotrophic microaerophilic FeOB (6,10,17,59), strongly suggesting that the 16S and cbbM sequences also represent this metabolism. The physiological characteristics of OYT1 are similar to those of other freshwater microaerophilic FeOB isolates growing at circumneutral pH, such as R-1, S. lithotrophicus strains ES-1 and LD-1, G. capsiferriformans strain ES-2, and Sideroxydans paludicola strain BrT (6,10,17).…”
Section: Discussionmentioning
confidence: 99%
“…Sideroxydans spp. are prevalent in iron-rich environments and prefer microaerophilic conditions (Emerson and Moyer, 1997;Weiss et al, 2007); furthermore, they have been detected in acidic peatlands indicating that some species are acidophilic or acid-tolerant (Lü decke et al, 2010). A previous study indicated that Gallionella ferruginea could perform autotrophic nitrate-dependent Fe(II) oxidation (Gouy et al, 1984), but no further studies with Gallionella have investigated this capability; however, studies have shown a complex distribution of Gallionella in relationship to the redox zonation in wetland soils (Wang et al, 2009), which is consistent with the existence of anaerobic phylotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In the deeper layers of the sediment, Fe(II) oxidation is known to happen in the rhizosphere of plants by root released O 2 (Frenzel et al, 1999;Neubauer et al, 2007;Weiss et al, 2007) or in the sediment by nitrate-dependent Fe(II) oxidation by organisms growing either autotrophically or heterotrophically (Straub et al, 1996;Benz et al, 1998). An increasing body of literature over the last decade has shown that biogenic Fe(II) oxidation could have a more prominent role in iron cycling than considered previously, especially in low-pH environments (Lu et al, 2010;Lü decke et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some Gal221-labeled cells were bean-shaped and attached to the end of helical stalks, typical of G. ferruginea, whereas other Gal221-labeled cells were more rod-shaped, consistent with the morphology of Sideroxydans spp., associated with particulate Fe(III)-oxyhydroxides (Weiss et al, 2007). It is important to note that several pure cultures of Gallionellales-related FeOB do not form stalks or identifiable Fe(III)-oxyhydroxide structures (Emerson and Moyer, 1997;Weiss et al, 2007;Lü decke et al, 2010); thus, the absence of stalks does not necessarily reflect the absence of this FeOB family. This may explain why Gallionellales FISH counts decreased with stalk disappearance but remained present throughout the remainder of the sampling season (Figure 2).…”
Section: Repeated Seasonal Development Of Ld Iron Matsmentioning
confidence: 99%